Determination of the optimal parasitoid‐to‐host ratio for efficient mass‐rearing of the parasitoid, Sclerodermus pupariae (Hymenoptera: Bethylidae). (10th March 2016) - Wei, K.; Gao, S. K.; Tang, Y. L.; Wang, X. Y.; Yang, Z. Q.
Abstract: Sclerodermus pupariae Yang et Yao (Hymenoptera: Bethylidae) is used as a potential biocontrol agent for several buprestid and cerambycid larvae. This study aimed to enhance the efficiency of mass‐rearing of this parasitoid by investigating the fitness gain of this bethylid wasp, including the proportion of successful parasitism and development, brood size, sex ratio, proportion of winged female offspring, body size and longevity of female offspring, under eight different maternal parasitoid density treatments using Thyestilla gebleri Faldermann as host in the laboratory. The results indicated that the foundress densities did not affect the parasitism or emergence rate of this parasitoid. Brood size of the parasitoids increased significantly when the number of maternal wasps ranged from one to four. However, further increases in foundress number did not affect the parasitoid brood size. The sex ratios of S. pupariae were always female‐biased. The proportions of male in the progeny colonies were <10% throughout all experimental treatments. The percentage of winged female progeny was not significantly influenced by the density of adult maternal parasitoids. Body sizes of parasitoids significantly declined with increasing maternal parasitoid densities. Although the parasitoid body size reduced when maternal wasp number was higher, it could be compromised by the relatively higher number of female offspring produced. Further, more than 70% of the parasitoids remained alive when they were stored at 12°C for four months throughout the experiments. These findings suggest that exposure of four female wasps to a single host larva would result in the highest fitness of S. pupariae . Our findings might provide a new approach to enhance the efficiency of mass‐rearing of this bethylid wasp.